Economic violence and its associated factors on Filipina women: Evidence from the 2013 and 2017 Philippines national demographic and health survey - Roque, John Robert Lim (Animo Repository, 2022)
Economic violence against women has largely been neglected in most literature, despite intimate partner violence being one of the more pervasive social problem globally. Most empirical studies focus on physical, emotional, or sexual abuse, or a combination of these – necessitating the study of economic violence, particularly in low- and middle-income nations such as the Philippines. While other studies looked into the association between economic violence and other demographic and socio-economic characteristics in a year and did not consider husband/partner’s alcohol consumption, we examine numerous factors that are associated with the occurrence of economic violence to women in the Philippines between two time periods. In the National Demographic and Health Surveys, the binary logistic regression model was applied to a pooled cross-sectional weighted data from women aged 15 to 49 years old in the Philippines, in 2013 and 2017. The analysis of this study only includes weighted observations of women who are currently in a union. Results showed that economic violence is strongly associated with other forms of violence – physical, emotional, and sexual violence. Measures of socio-economic inequalities and other explanatory variables have shown that having more children, lower educational attainment, and having a husband that drinks alcohol were significantly associated with increasing the odds of experiencing economic violence. This suggests that there is a need to address the factors that contribute to economic violence to put a stop to the prevalence of economic abuse against women in the Philippines.